Born similar, develop apart: Evidence on Chinese hybrid exporters - Xiaodong Bie; Andrea Ciani (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
Processing trade is often a leading channel for the internationalization of firms in emerging economies and to foster their integration in Global Value Chains (GVCs). This study investigates differences in performance among Chinese exporting firms differently involved in processing trade. We distinguish firms pursuing only processing trade from firms which are also involved in ordinary trade (hybrid exporters). We rely on detailed balance sheet data and on customs data on firm transactions for the period 2000-2007. Results show that hybrid exporters outperform firms exclusively involved in processing trade in terms of value added, productivity, profits, product quality, and revenue in the different export destinations. We find that this difference in performance is associated with the increase in Chinese domestic value added. Hybrid exporters can rely to a larger extent than purely processing exporters on domestic inputs which, during this period, benefited from remarkable increases in productivity.
Keywords: F01; F10; F14; O1; 330; Processing trade; Firm productivity; Domestic value added